The Association Between Antioxidant Enzyme Polymorphisms with Type 2 Diabetes Mellitus in Jazan Province - Habibullah MM; Hurubi A; Hakamy AO; Alwadani AAJ; Atti IM; Alothaid H; Shamlan G; Aldughaim M; Kaabi YA; Alhazmi A; Hamali H (Diabetes, Metabolic Syndrome and Obesity)
Mahmoud M Habibullah,1 Ali Hurubi,1 Ali O Hakamy,2 Abbas Ali Jaber Alwadani,3 Ibrahim Mohammed Atti,3 Hani Alothaid,4 Ghalia Shamlan,5 Mohammed Aldughaim,6 Yahia A Kaabi,1 Alaa Alhazmi,1 Hassan Hamali1 1Department of Medical Laboratory Technology, College of Nursing and Health Sciences, Jazan University, Jazan, Saudi Arabia; 2Nursing Department, College of Nursing and Health Sciences, Jazan University, Jazan, Saudi Arabia; 3Department of Laboratory and Blood Bank, Prince Mohammed Bin Nasser Hospital, Ministry of Health, Jazan, Saudi Arabia; 4Department of Basic Medical Science, Faculty of Applied Medical Sciences, Al-Baha University, Al-Baha, Saudi Arabia; 5Department of Food Science and Nutrition, College of Food and Agriculture Sciences, King Saud University, Riyadh, Saudi Arabia; 6Research Centre, King Fahad Medical City, Riyadh, Saudi ArabiaCorrespondence: Mahmoud M Habibullah, Department of Medical Laboratory Technology, College of Nursing and Health Sciences, Jazan University, 6514 Makkah Al Mukarrama Road, Jazan, 82822, Saudi Arabia, Email mhabibullah@jazanu.edu.saIntroduction: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by persistent hyperglycemia, which results in initiates oxidative stress and disrupts various cellular pathways. In this study, we examined the relationship between polymorphisms in antioxidant enzymes, specifically glutathione peroxidase 1 (GPx1) and catalase (CAT), and the susceptibility to T2DM in a Saudi population from the Jazan Province.Methods: A total of 419 participants were evaluated, including 247 T2DM patients and 172 controls. They were genotyped for the GPx1 Pro198Leu and CAT-262C/T polymorphisms by a PCR-based method.Results: The results indicated that individuals with the CAT T/T genotype had a 60% lower likelihood of developing T2DM compared with those harboring the C/C genotype (uOD 0.4; 95% CI 0.2– 0.8, p = 0.04); however, no significant association was observed between the GPx1 polymorphism and T2DM.Discussion: The results suggest that CAT polymorphism may confer a protective effect against T2DM, whereas the GPx1 polymorphism appears not to be a determinant of T2DM susceptibility in this population. Further studies including larger and more diverse cohorts are necessary to validate these results and elucidate the underlying mechanisms. Understanding the genetic factors that contribute to T2DM is essential for developing targeted preventive and therapeutic strategies.Keywords: type 2 diabetes mellitus, antioxidant enzymes, glutathione peroxidase 1, catalase, polymorphism, Saudi population